Hadith #5181 - Sunan Abi Dawud - Abdul Qahir bin Shu'iab bin al-Habhab عبد القاهر بن شعيب بن الحبحاب; Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; Hameed bin Hilal حميد بن هلال; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Zayd bin Akhzm زيد بن أخزم (Sunan Abi Dawud)
Abu Musa asks permission, al-Ash’ari ask permission, and ‘Abd Allah b. Qais asks permission, but it was not granted to him. So he went away and ‘umar sent for him saying: what did you return? He replied: The Messenger of Allah (May peace be upon him) said: When one of you asks permission three times and it is not granted to him, he should go away. He said: Establish the proof of it. He went, came back, and said; This is Ubayy. Ubayy said: ‘Umar, do not be an agony for the Companions of t
Grade: Hasan